PENGARUH FERMENTASI TERHADAP KUALITAS PROBIOTIK DALAM YOGHURT SUSU KAMBING - Umbang Arif Rokhayati; Sri Yenny Pateda; Muhammad Sayuti M; Tri Ananda Erwin Nugroho (Universitas Negeri Gorontalo, 2026)
The purpose of this study was to determine and understand the effect of the fermentation process on the quality of probiotics in goat milk yogurt, in order to obtain the optimal formulation and fermentation conditions for producing yogurt products with high functional value that are suitable for development as probiotic foods. This study was an experimental study with a completely randomized design (CRD), using fermentation time variation as the treatment. The independent variables are fermentation time (4 hours, 6 hours, 8 hours, 10 hours), while the dependent variables are probiotic viability, physicochemical characteristics, and organoleptic properties. Based on the research that has been conducted, it was found that the lowest viability value of lactic acid bacteria (LAB) was recorded in the 4-hour fermentation (1.9 × 10⁵ CFU/mL), while the highest viability occurred in the 10-hour fermentation (6.5 × 10⁶ CFU/mL). The pH value of yogurt decreases as fermentation time increases. The highest pH was found in the 4-hour fermentation (4.74), while the lowest pH occurred in the 10-hour fermentation (3.86). The organoleptic (hedonic) test results showed that the most preferred taste was obtained from 6 hours of fermentation (hedonic value of 2.28); the most preferred aroma was obtained from 4 hours of fermentation (hedonic value of 1.40); and the most preferred texture was obtained from 8 hours of fermentation (hedonic value of 1.72). Overall, fermentation time has a significant effect on the quality of goat milk probiotic yogurt, both in terms of BAL viability, acidity (pH), and sensory (organoleptic) characteristics, with the best balance between probiotic quality and consumer acceptance at 10 hours of fermentation.